Accelerating motor skill acquisition for bicycle riding in children with ASD: A pilot study - Hawks, Zoë (J Autism Dev Disord, 2020)
Motor impairment is common in autism spectrum disorder (ASD) and, as such, a potential target for interventions to improve adaptive functioning. This study investigated motor skill acquisition in children with ASD (n = 15, 12 males; ages 7 – 16 years) during iCan Bike Camp, a one-week, community-based intervention (5×75-minute sessions) to teach independent bicycle riding. After completing the camp’s task-oriented, individualized training program, all participants demonstrated motor skill acquisition on the bicycle, and nine participants rode independently at least 70 feet. Exploratory analyses showed that motor coordination and social communication correlated with rates of skill acquisition. These findings indicate the feasibility and efficacy of brief, community-based motor interventions to teach bicycle riding—an important developmental skill supporting adaptive functioning—to children with ASD.